The Basic Understory: A Curriculum of Interrelation - Sameshima, Pauline (Journal of the Canadian Association for Curriculum Studies, 2018)
This editorial is an inquiry into the curriculum of interrelation. In preparation of the articles for this issue, I was struck by the spiritual, ecological, and genealogical resonances in the complex search for meaning. My makings invite you on a thread that networks here and there in a synaptic ontological question of re-storing experience in the languages we know. Through reverence, restoration, reflection and reparation, how might we find grace in the curriculum of learning life? What is the understory of education?